Elucidating the role of eIF6 in the endothelial response to shear stress - Simpson, L (2020)
Haemodynamic forces generated by blood flow are critical determinants of vascular function in health and disease. Fluid shear stress (FSS) is defined as a force per unit area and is generated by blood flowing parallel to the vessel wall. FSS highly influences the endothelial cell (EC) phenotype. ECs lining straight vessel regions are exposed to steady laminar FSS which induces cytoskeletal alignment and this promotes a protective, anti-inflammatory EC phenotype. Conversely, ECs situated at vascular branch points or curvatures are exposed to complex flow patterns, such as flow reversal, oscillations, low flow and turbulence, which promotes inflammatory gene expression, high proliferation rates and a lack of cytoskeletal alignment. Given the dynamic mechanical environment that ECs are exposed to, remodelling of their cytoskeleton represents an important central cellular function, yet the mechanisms involved remain to be fully elucidated. Recent evidence has shown that components of the protein translation machinery such as ribosomes and eukaryotic initiation factors (eIFs) are closely associated with the cell cytoskeleton. However, the importance of this interaction in regulating the EC phenotype and the relationship between haemodynamics and translational control are largely unexplored. The aim of my thesis project therefore was to investigate the differential effects of laminar and disturbed FSS on protein translation signalling and cytoskeletal remodelling and how one initiation factor, eIF6, mediates these processes. Previous work from the lab has shown that eIF6 co-localises along the Z-disks in cardiomyocytes but its role and potential function in EC biology has not been elucidated. The key findings from this work indicate an important novel role for eIF6 in mediating the EC response to shear stress including regulation of cytoskeletal alignment, focal adhesion dynamics and cell proliferation. Further, my results show that eIF6 itself is flow regulated and plays a differential role in EC protein translation mechanisms under laminar and disturbed FSS. The work outlined in this thesis provides a better understanding of how translational components like eIF6 regulate EC cellular processes which are relevant for vascular health and disease.